In Memoriam – Yang Xiaoping - Editor, CJAL (Columbia Journal of Asian Law, 1989)
It is with the deepest sadness that we report the death of our friend and colleague, Yang Xiaoping, who died of a massive cerebral hemorrhage on September 24, 1989. Xiaoping served for two years on the staff of the Journal of Chinese Law, most recently as Translations Editor.